RATIONAITY AND INTERVENTION EFFICIENCY OF CLINICAL PHARMACIST IN USAGE PAINKILLERS AFTER OPERATION (Vietnam Journal of Community Medicine, 2021)
Objectives: To evaluate the rationality and effectiveness of clinical pharmacist’s intervention in the use of painkillers for post-operative pain treatment at the General Surgery Department of Cai Nuoc General Hospital. Objects and methods: Cross-sectional descriptive study on 172 patients (patients) undergoing surgery at General Surgery Department, Cai Nuoc General Hospital. Results: There were 38.95% of patients studied with adverse effects when using painkillers. The average duration of painkiller use after surgery was 5.6 ± 4.0 days. The differences in the mean time to take the drug between the 2 groups were statistically significant. VAS pain scores of the study samples tended to decrease gradually over 1, 3, 5, 7 days after surgery. On 2 research groups, in general, the average VAS score after 1 day surgery was 4.2 ± 1.9 points and after 7 days was 1.1 ± 0.8 points. Increase the reasonable rate in choosing drugs group 2 with reasonable rate was had a reasonable rate of 68.18%, much higher than group 1 with 46.43%. Conclusion: The incidence of adverse effects was low. The differences in the mean time to take the drug 70.45%, much higher than group 1 with 42.86%; drug dose, group 2 had reasonable rate was 82.95%, much higher than group 1 with 55.95%; the rationality of drug use, group 2 between the 2 groups were statistically significant. VAS pain scores of the study samples tended to decrease gradually over 1, 3, 5, 7 days after surgery. Increase the rationality of drug selection, drug dosage, and general rationality of post-operative pain treatment.
Keywords: Reasonability, effectiveness of intervention, painkiller after surgery